Mental and Physical Health among Homeless Sexual and Gender Minorities in a Major Urban US City - Flentje, Annesa (J Urban Health, 2016)
Sexual and gender minorities have been shown to have greater rates of mental health, substance use disorders, and specific types of health problems compared to heterosexuals. Among the homeless population in several US urban areas, sexual and gender minorities are overrepresented but few studies have examined the mental and physical health status of homeless sexual and gender minorities, with studies on homeless gender minorities being particularly hard to find. Using survey data obtained from the city and county of San Francisco (2015 Homeless Survey), this study examined differences in causes of homelessness, physical and mental health problems, and domestic violence among homeless sexual and gender minorities and their heterosexual and cisgender (i.e., non-transgender) counterparts, respectively. Lesbians and bisexual women, and gay and bisexual men did not differ from their cisgender heterosexual counterparts. Cisgender men who identified as queer or “other” in response to sexual orientation questions had higher rates of psychiatric problems and posttraumatic stress disorder, while cisgender women who identified as queer or “other” had higher rates of psychiatric problems and drug and alcohol use. Transgender men who were homeless were found to be particularly at risk for physical health problems, mental health problems, and domestic violence or abuse. Transgender women were more likely to report posttraumatic stress disorder. This study suggests that transgender men and cisgender sexual minority men and women who identify as queer or “other” are groups among the homeless that may benefit from increased outreach and services.